Influence of methotrexate, TNF blockers and prednisolone on antibody responses to pneumococcal polysaccharide vaccine in patients with rheumatoid arthritis - Meliha C Kapetanovic; Tore Saxne; Åke Sjöholm; Lennart Truedsson; G. Jönsson; P. Geborek (2005)
Objective. To compare antibody responses to 23-valent pneumococcal vaccine (Pneumovax®) in controls and patients with established rheumatoid arthritis (RA) treated with TNF blockers, methotrexate (MTX) or a combination of both.